Endoscopic ultrasound-guided hepaticogastrostomy or hepaticojejunostomy without dilation using a stent with a thinner delivery system - Maehara, Kosuke; Hijioka, Susumu; Nagashio, Yoshikuni; Ohba, Akihiro; Maruki, Yuta; Suzuki, Hiromi; Sone, Miyuki; Okusaka, Takuji; Saito, Yutaka (Endoscopy International Open, 2020)
Background and study aim Use of endoscopic ultrasound-guided biliary drainage (EUS-BD) has recently increased. In EUS-BD, after puncturing the bile duct, dilation is performed and the stent is deployed. Due to adverse events (AEs) such as unexpected displacement of the guidewire, simplified procedures are required. Currently, stents with small-diameter delivery systems are being rapidly developed, expanding the possibilities for of EUS-BD without dilation. In this retrospective study, we aimed to evaluate the success rates and AEs in patients who underwent EUS-guided hepaticogastrostomy (EUS-HGS) or EUS-guided hepaticojejunostomy (EUS-HJS) without dilation.Patients and methods Six consecutive patients with malignant biliary obstruction and failed transpapillary BD underwent EUS-HGS or EUS-HJS without dilation, deploying a 6-mm fully-covered self-expandable metallic stent with a 6-Fr delivery system.Results The technical and clinical success rates were 100 %. There was one case each of stent migration and stent occlusion, and no other AEs were noted.Conclusions EUS-HGS or EUS-HJS without dilation using a stent with a 6-Fr delivery system had high technical and clinical success rates; however, additional cases are required to validate the study findings.